STATISTICAL MODELING OF INTERNALLY DISPLACED PERSONS (IDPS) IN BORNO STATE: TRENDS, CAUSES, AND PREDICTIVE ANALYSIS (2009 - 2025) - Gloria Oduifa Otouaye (World Journal of Biology Pharmacy and Health Sciences, 2026)
This study, titled “Statistical Modeling of Internally Displaced Persons (IDPs) in Borno State: Trends, Causes, and Predictive Analysis (2009–2025)”, investigates the historical trends, root causes, and future projections of internal displacement in Borno State, Nigeria. The research was guided by the following objectives: (i) to analyze the historical trends of IDPs in Borno State, (ii) to identify the principal causes of displacement, and (iii) to develop statistical models to predict future displacement patterns. A quantitative research design was adopted. Data was collected through structured questionnaires distributed among 90 displaced persons in Borno State and supplemented by secondary sources from government and humanitarian agencies. Analytical tools included descriptive statistics, time series forecasting using ARIMA (1,1,1), and multiple regression analysis to determine the impact of conflict intensity on IDP numbers. The findings revealed that the Boko Haram insurgency and associated military operations were the primary causes of internal displacement in the state, as confirmed by 91.1% of respondents. The displacement trend peaked between 2013 and 2016, corresponding to intensified violence and military campaigns. From 2009 to 2025, the number of IDPs increased significantly from 515,000 in 2009 to over 1.24 million in 2025. Time series forecasting projected that, without intervention, IDP figures could exceed 1.5 million by 2030. Regression analysis showed that each unit increase in conflict intensity led to an approximate rise of 95,400 IDPs, confirming a strong positive correlation between insurgency and displacement. These findings indicate a cyclical and escalating pattern of displacement directly tied to security dynamics in the region. The study concludes that insurgency remains the most significant driver of internal displacement in Borno State. It is recommended that government authorities enhance security and counterinsurgency efforts, increase humanitarian assistance, and adopt predictive, data-driven approaches to improve planning and response. Furthermore, economic recovery programs and targeted vocational training in IDP camps are essential for reducing dependency and restoring livelihoods.